A serious games development framework through application of software development life cycle model - Siti Normaziah, Ihsan; Tuty Asmawaty, Abdul Kadir (2017)
Developments of software projects involves standards process in each phase of procedure. Each activity led the software experts control the process of development including time and cost during the development. The process will help them in managing and improve the development process. Nowadays, the term of serious games is becoming popular in many industries such as healthcare, tourism, education and so on. Researchers and developers agree that the purpose of playing serious games is not limited to entertainment only. The goal is not just playing for pure entertainment, but also convey information, educate, persuade and provide a call to action among other things. Seeing the growth of industries in serious games and the available structures, tools and process models, methodical approach to the software engineering activities for serious games development should identify. In this paper, we propose a suitable framework development model that adopt from Software Development Life Cycle (SDLC) for the serious games. It is needed to inspect this domain and adopt the software processes that best serve the developers and is flexible enough to address the different requirement of such applications.